Adapting evidence-informed population health interventions for new contexts: a scoping review of current practice - A. Movsisyan; L. Arnold; L. Copeland; R. Evans; H. Littlecott; G. Moore; A. O'Cathain; L. Pfadenhauer; J. Segrott; E. Rehfuess (BMC, 2021)
Abstract Background Implementing evidence-informed population health interventions in new contexts often requires adaptations. While the need to adapt interventions to better fit new contexts is recognised, uncertainties remain regarding why and when to adapt (or not), and how to assess the benefits (or not) of adaptation. The ADAPT Study aims to develop comprehensive guidance on adaptation. This scoping review informs guidance development by mapping and exploring how adaptation has been undertaken in practice, in public health and health services research. Methods We searched seven databases from January 2000 and October 2018 to identify eligible studies for this scoping review and a related systematic review of adaptation guidance. We mapped the studies of adaptation by coding data from all eligible studies describing the methods, contexts, and interventions considered for adaptation. From this map, we selected a sample of studies for in-depth examination. Two reviewers extracted data independently into seven categories: description, key concepts, types, rationale, processes, evaluation methods, evaluation justification, and accounts of failures and successes. Results We retrieved 6694 unique records. From 429 records screened at full text, we identified 298 eligible studies for mapping and selected 28 studies for in-depth examination. The majority of studies in our map focused on micro- (i.e., individual-) level interventions (84%), related to transferring an intervention to a new population group within the same country (62%) and did not report using guidance (73%). Studies covered a range of topic areas, including health behaviour (24%), mental health (19%), sexual health (16%), and parenting and family-centred interventions (15%). Our in-depth analysis showed that adaptation is seen to save costs and time relative to developing a new intervention, and to enhance contextual relevance and cultural compatibility. It commonly follows a structured process and involves stakeholders to help with decisions on what to adapt, when, and how. Conclusions Adaptation has been undertaken on a range of health topics and largely in line with existing guidance. Significant gaps relate to adaptation of macro- (e.g., national-) level interventions, consideration of programme theories, mechanisms and contexts (i.e., a functional view of interventions), nuances around stakeholder involvement, and evaluation of the adapted interventions. Registration Open Science Framework, 2019, osf.io/udzma.